Analysis of Geographical Information System (GIS) design aplication in the Fire Department of Depok City - Andri Supriadi; Teddy Oswari (Technium Social Sciences Journal, 2020)
Depok City is one of the cities that is vulnerable to fire disasters. The Depok City Fire Department feels the need for a system that can assist in the handling and management of fire disasters. This system must be the right system to solve existing problems. Researchers have created many new systems. One of them is Geographic Information System (GIS) is a special information system for managing data that has spatial information. This research purposes to analyze and design a Geographic Information System (GIS) aimed at assisting the Depok City Fire Department that is desktop-based using the waterfall method. With the application of this Geographic Information System (GIS) aims to help accelerate the processing of fire reports on decision making, presenting spatial and non-spatial data that is more organized and can be updated also makes it easier to find new locations of fire stations , hydrants, fire-prone points, and flood-prone points.